A Novel Dynamic Weight Neural Network Ensemble Model. (30th August 2015) - Li, Kewen; Liu, Wenying; Zhao, Kang; Shao, Mingwen; Liu, Lu
Abstract : Neural network is easy to fall into the minimum and overfitting in the application. The paper proposes a novel dynamic weight neural network ensemble model (DW-NNE). The Bagging algorithm generates certain neural network individuals which then are selected by the K -means clustering algorithm. In order to solve the problem that K -value cannot be selected automatically in the K -means clustering algorithm when conducting the selection of individuals, the K -value optimization algorithm based on distance cost function is put forward to find the optimal K -values. In addition, for the integrated output problems, the paper proposes a dynamic weight model which is based on fuzzy neural network with accordance to the ideas of dynamic weight. The experimental results show that the integrated approach can achieve better prediction accuracy compared to the traditional single model and neural network ensemble model.